Extrusion apical de detritus durante el tratamiento endodóntico - Pina-Vaz, Irene (2008)
The authors made a literature review about the causes of the apical extrusion of debris, during endodontic treatment. In the root canal instrumentation there is always, besides the strict control of the working lenght, the possibility that dentin chips and residual pulp tissue can be forced apically through the apical foramen. Those, contaminated or not contaminated, materials can lead to an inflammatory and pos-operative reaction, known as flare-up. To avoid the apical extrusion and minimize flare-ups, some methods are proposed, as the selection of instrumentation techniques that extrude less amounts of debris apically and the respect for the aseptic chain during intracanal procedures. The authors conclude that although all the instrumentation techniques cause some degree of extrusion, crow-down techniques and those which involve rotary movements, significantly reduce the amount of debris extruded.